Green Enterprises: A pathway to Women’s Economic Empowerment - Thakuri, Usha; Baral, Srijana; Lama, Kanchan; Khatri, Aarati (Journal of Forest and Livelihood, 2024)
Approximately 80 per cent of Nepal’s rural population, predominantly women, rely on NonTimber Forest Products (NTFPs) for their livelihoods. Despite ample studies on NTFPs, their role in economically empowering women is scant. Taking the case from four community forests in Nawalparasi, this paper examines how NTFPs such as the leaves of Shorea robusta (Sal) and Phoenix loureiroi Kunth (Thakal) are evident means to empower women. To understand how the process empowered women, the researchers emphasise their firsthand observations to serve as valuable data, complemented by key informant interviews (n=55), workshops (n=2), and formal and informal observations.. The results show that the annual harvestable yield of Sal leaves (3 CFs) and Thakal leaves are 207020.75 kg and 5089.35 kg respectively. This would create 448565 days of green employment opportunities for marginalised women and men. The research concludes that involving women in the inventory process aids in enhanced technical forestry knowledge, increased control over access to resources, attitude change, and shifts in power relations Hence, incorporating NTFPs in community forest operational plans and upscaling is recommended to promote economic, technical, and socio-cultural empowerment for both women and men.